2019
DOI: 10.1016/j.jse.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in patients undergoing surgery for shoulder instability: a Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Instability cohort study

Abstract: Hypothesis and background: Male sex has been identified as a risk factor for both primary shoulder dislocation and recurrent instability, and male patients more often undergo surgery for instability. Despite published discrepancies between sexes regarding the incidence and surgical rates of shoulder instability, there is little detail on the differences in presentation, mechanism of injury, and intraoperative findings. The purpose of this study was to explore these differences. Methods: Prospective baseline da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“… 22 , 23 Although there is a lower incidence of shoulder instability in women, this population is still representative and is often associated with lower rates of return to sports. 16 , 19 , 21 , 22 Studies with athletes of both sexes often have female participants who experience longer periods of complaints of pain after the procedure or those who never return to the practice of sports. 9 , 25 However, this population is under-represented in the literature on orthopedic studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 , 23 Although there is a lower incidence of shoulder instability in women, this population is still representative and is often associated with lower rates of return to sports. 16 , 19 , 21 , 22 Studies with athletes of both sexes often have female participants who experience longer periods of complaints of pain after the procedure or those who never return to the practice of sports. 9 , 25 However, this population is under-represented in the literature on orthopedic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Aesthetic satisfaction after the Latarjet procedure has been discussed and analyzed over the past few years. 19 The deltopectoral approach to the shoulder, located on an interneural plane between the musculocutaneous and axillary nerves, is the standard approach for the open Latarjet procedure. 17 , 28 The incision leaves a scar at an exposed area of the body that may be related to lower aesthetic satisfaction, especially for young patients, or cicatrization complications such as keloids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the sexes associated with shoulder instability has been reported previously. 14 , 15 , 19 , 26 , 35 Female athletes participating in soccer, basketball, and rugby have been reported to have a higher risk of shoulder dislocation compared with their male counterparts. 23 , 27 The Multicenter Orthopaedic Outcomes Network study group reported that capsular laxity was higher in females, whereas labral pathology and bone defect were higher in males.…”
Section: Discussionmentioning
confidence: 99%
“…20 Multidirectional instability is often associated with ligamentous laxity, whereas unidirectional instability 12,19 is more traumatic in etiology. 9,14,19 The frequency, etiology, chronicity, severity, and direction 12 of instability are other important descriptors.…”
mentioning
confidence: 99%